Female images in the works of Askad Mukhtar "Roots" and Vyacheslav Shugaev "Russian Venus" - Kalonova Nargiza Nurzhovna; Sultanova Quvonchoy Yakubboy qizi (Peerian Journals Publishing, 2022)
the article analyzes the semantic features of artistic comparison: the most frequent thematic groupings of comparisons are identified that contribute to the creation of a female image in Russian and Uzbek literature
Keywords: Female image; artistic comparison; object of comparison; thematic group